FGF21 Levels in Pheochromocytoma/Functional Paraganglioma - Klímová, Judita; Zelinka, Tomáš; Rosa, Ján; Štrauch, Branislav; Haluzíková, Denisa; Haluzík, Martin; Holaj, Robert; Krátká, Zuzana; Kvasnička, Jan; Ďurovcová, Viktorie; Matoulek, Martin; Novák, Květoslav; et al. (Cancers, 2019)
Fibroblast growth factor 21 (FGF21) is a hepatokine with beneficial effects on metabolism. Our aim was to evaluate the relationship between the serum FGF21, and energy and glucose metabolism in 40 patients with pheochromocytoma/functional paraganglioma (PPGL), in comparison with 21 obese patients and 26 lean healthy controls. 27 patients with PPGL were examined one year after tumor removal. Basic anthropometric and biochemical measurements were done. Energy metabolism was measured by indirect calorimetry (Vmax-Encore 29N). FGF21 was measured by ELISA. FGF21 was higher in PPGL than in controls (174.2 (283) pg/mL vs. 107.9 (116) pg/mL; p < 0.001) and comparable with obese (174.2 (283) pg/mL vs. 160.4 (180); p = NS). After tumor removal, FGF21 decreased (176.4 (284) pg/mL vs. 131.3 (225) pg/mL; p < 0.001). Higher levels of FGF21 were expressed, particularly in patients with diabetes. FGF21 positively correlated in PPGL with age (p = 0.005), BMI (p = 0.028), glycemia (p = 0.002), and glycated hemoglobin (p = 0.014). In conclusion, long-term catecholamine overproduction in PPGL leads to the elevation in serum FGF21, especially in patients with secondary diabetes. FGF21 levels were comparable between obese and PPGL patients, despite different anthropometric indices. We did not find a relationship between FGF21 and hypermetabolism in PPGL. Tumor removal led to the normalization of FGF21 and the other metabolic abnormalities.
Keywords: diabetes mellitus; FGF21; calorimetry; pheochromocytoma; obesity; paraganglioma; energy metabolism